2012
DOI: 10.1089/aid.2010.0317
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-15 and Interleukin-15Rα in Monocytes of HIV Type 1-Infected Patients with Different Courses of Disease Progression

Abstract: Interleukin-15 (IL-15) enhances the effector mechanisms of anti-HIV immune responses and thus is considered a potential adjuvant of HIV-1 vaccine. However, there are a lack of data concerning the relationships between IL-15 expression and regulation in HIV-1-infected patients and the course of disease progression. We found that IL-15, but not IL-15Ra, is expressed at significantly higher levels in the CD14 + monocytes [stimulated or not with interferon (IFN)-c] of long-term nonprogressors (LTNP) than in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Consistent with prior studies, plasma sCD14 correlated not only with IL-6 [18] , [55] , but also with IL-15 [22] , [56] . Elevated IL-15 is associated with higher plasma VL during acute HIV infection [38] , while IL-15 is expressed at higher levels in monocytes from HIV-infected long-term nonprogressors compared to progressors or uninfected controls [57] . IL-15 is a Th1 cytokine expressed on monocytes upon activation that shares activities with IL-2, such as stimulation of T cell proliferation and activation, but also stimulates cell adhesion and production of proinflammatory cytokines [58] and NK cell functions, including secretion of IFNγ and CCR5 ligands [59] , [60] .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies, plasma sCD14 correlated not only with IL-6 [18] , [55] , but also with IL-15 [22] , [56] . Elevated IL-15 is associated with higher plasma VL during acute HIV infection [38] , while IL-15 is expressed at higher levels in monocytes from HIV-infected long-term nonprogressors compared to progressors or uninfected controls [57] . IL-15 is a Th1 cytokine expressed on monocytes upon activation that shares activities with IL-2, such as stimulation of T cell proliferation and activation, but also stimulates cell adhesion and production of proinflammatory cytokines [58] and NK cell functions, including secretion of IFNγ and CCR5 ligands [59] , [60] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant changes in this pathway was the effective and systematic down-regulation of genes encoding pro-inflammatory cytokines, including IL-1B, IL-6, IL-8, TNF-α, in the viremia group. Interestingly, the core-enriched gene IL-15 shares many activities with IL-2 and is down-regulated in patients with viremia, and was also found to be expressed at significantly higher levels in LTNPs monocytes than in people with HIV progression ( 75 ). Finally, a study has shown that at least one host genetic factor (HLA, chemokine receptors is associated with slow HIV progression ( 76 ).…”
Section: Participation In the Innate Immune Pathway Of Hiv Infection ...mentioning
confidence: 99%
“…In a previous study of the same group, IL-15 priming was shown to induce a significant increase of IFN-gamma production in both viremic and aviremic HIV-positive patients [ 132 ]. Tarkowski et al [ 133 ] found that the expression of IL-15, but not of its receptor IL-15R α , was significantly higher in the CD14+ monocytes of long-term nonprogressors than in those of HIV-1 progressors or healthy controls; differences in IL-15 expression between patients with different courses of HIV infection may be indicative of a potential use of this cytokine as a therapeutic agent.…”
Section: Potential Strategies To Reduce Residual Viremia and Enhanmentioning
confidence: 99%